Proses Pembebasan Lahan pada Pelaksanaan Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum Berdasarkan Undang-undang Nomor 2 Tahun 2012 Tentang Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum (Studi Kasus pada Kantor Pertanahan Kota Tangerang Selatan) - Hodidjah Hodidjah; Aria Dimas Harapan (Rechtsregel : Jurnal Ilmu Hukum, 2020)
Land procurement for development for the public interest of the Serpong - Cinere toll road has been started since 2014. The construction of this toll road is very urgent to do considering the traffic flow from Serpong, South Tangerang to the airport is quite far and getting denser. This research on legal writing aims to determine the land acquisition process in the implementation of land acquisition for the public interest of the Serpong - Cinere toll road and what rights grounds are used as the basis for the community to obtain compensation and what obstacles are faced in its implementation.The approach method used in this paper is Juridical Empirical with analytical descriptive specifications, based on Law Number 2 of 2012 and Presidential Decree Number 71 of 2012 concerning Implementation of Land Acquisition for Development for Public Interest. The case raised was the identification and re-inventory because there were differences between the field map and the rights pad presented by the community so that it had to be re-measured according to the right base. This causes delays in the next stage in the land acquisition implementation process.The need for firmness in land acquisition executors at every stage so that the implementation of land acquisition can be in accordance with existing regulations and does not drag on, is also the need for public awareness in maintaining the boundaries of their land parcels accompanied by proof of ownership.